Global Yield Gap and Water Productivity Atlas (GYGA) for rice in Africa - CGIAR Research Program on Rice (2019)
Egypt, Ivory Coast, Madagascar, Rwanda, and Senegal were added to GYGA database. In total, yield gap data are avaialble in 13 countries in Africa.